FORMATION OF CULTURE OF READING AMONG STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS: CURRENT PROBLEMS AND RESEARCH (Scientific journal of the Fergana State University, 2023)
The article has analyzed the existing problems in the formation of culture of reading among students of higher education institutions. Some problems of the university's information-resource centers are studied among students and made suggestions and recommendations on the solutions. The university emphasizes that students are not just as a library student, but also readers and researchers.